Analysis of Differences in Mathematical Understanding of Class IV Students at UNISMUH Makassar Labschool Based on Learning Style - Sabrina, Sabrina; Widiyasari, Ririn; Nursalim, Nursalim (Universitas Muhammadiyah Makassar, 2025)
This research aims to analyze differences in mathematical understanding of fourth grade students at UNISMUH Makassar Labschool based on their learning styles. The background to this research stems from various problems found in the field, such as students' low mathematical understanding, teachers' lack of understanding of learning styles, and the lack of research related to learning styles at the elementary school level. This research uses a descriptive qualitative approach with phenomenological methods to explore students' subjective experiences in understanding integer material based on visual, auditory and kinesthetic learning styles. The research results show that students with an auditory learning style tend to excel in solving problems verbally and narratively, while visual students are better at understanding basic concepts through pictorial representations, but have difficulty in advanced applications. Kinesthetic students show moderate comprehension, depending on the physical activity and props used. Although differences were found in the level of mathematical understanding between learning styles, these differences were not statistically significant. Thus, learning style is not the only determining factor in students' mathematical understanding, but it still needs to be considered in planning more adaptive learning.